Can existing mould growth models be used to predict mould growth on wooden claddings exposed to transient wetting?. (April 2019) - Lie, Solrun Karlsen; Thiis, Thomas K.; Vestøl, Geir I.; Høibø, Olav; Gobakken, Lone Ross
Abstract: Surface mould growth contributes to the colour changes of outdoor exposed wood over time. Modelling mould growth can thus help visualize wooden facades' colour development, which can improve facade design and service life. However, existing wood mould models do not consider transient wetting effects that occur outdoors due to precipitation and condensation. To address this, four mould models were evaluated using laboratory experimental data that included exposure to transient wetting. First, the models (the original and the updated VTT model, the biohygrothermal model and the mould resistance design (MRD) model) were evaluated for Scots pine sapwood. For this evaluation, the transient wetting effect was implemented in the models by using hourly wood surface relative humidity (RH), calculated from electrical resistance measurements, as input. This showed that the original and the updated VTT model gave best fit to the experimental data. However, further evaluation of these two models for more wood materials showed that the updated VTT model was sensitive to the choice of material parameters. Large discrepancies occurred when varying the material parameters in the updated VTT model. Finally, different estimates of RH were tested in the original VTT model. Using wood surface RH as input gave best fit to the experimental data, and ambient air RH gave poorest fit. Overall, the results indicate that the original VTT model is fairly reliable and can be used to predict mould growth on wooden claddings exposed to transient wetting as long as the wood surface climate is used as climatic input data. Highlights: Four existing mould growth models were evaluated using experimental data. Eight climatic conditions and eight wood materials were included in the evaluation. The transient wetting effect was implemented in the models by using wood humidity as input data. The original VTT model gave the most reliable estimates.